1998
DOI: 10.2118/98-09-06
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage of Oil Well Cement Slurries

Abstract: FIGURE 1: Principle of the shrinkage measurements.FIGURE 2: Total shrinkage of slurry T25. FIGURE 4: Total shrinkage of slurry W90. FIGURE 3: Total shrinkage of slurry T60. FIGURE 5: Total shrinkage of slurry W140.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In the actual wellbore, typical temperature and pressure are about 12 o C and 12 MPa (Yamamoto et al 2017), whereas the laboratory shrinkage test, whose data were used for model calibration, was conducted at approximately 20 o C and 2 MPa. The literature shows that cement shrinkage volume becomes greater when the temperature and pressure increases (Backe et al 1998;Reddy et al 2009). Hence the amount of shrinkage volume might be underestimated for Class G and RS cement.…”
Section: Discussionmentioning
confidence: 99%
“…In the actual wellbore, typical temperature and pressure are about 12 o C and 12 MPa (Yamamoto et al 2017), whereas the laboratory shrinkage test, whose data were used for model calibration, was conducted at approximately 20 o C and 2 MPa. The literature shows that cement shrinkage volume becomes greater when the temperature and pressure increases (Backe et al 1998;Reddy et al 2009). Hence the amount of shrinkage volume might be underestimated for Class G and RS cement.…”
Section: Discussionmentioning
confidence: 99%
“…Leakage of the gas into and through the cemented annulus in oil and gas wells can harm the environment and jeopardize well safety. A modest shrinkage of the cement slurry is thought to lessen the danger of gas migration. , …”
Section: Effect Of Nanosilica On the Properties Of Oil Well Cementmentioning
confidence: 99%
“…Cement volume shrinkage occurs due to cement hydration process. The volumes of cement shrinkage reported in the literature varies from 0.1% to 4.5% (Goboncan & Dillenbeck 2003;Backe et al 1998;Justnes et al 1995;Chenevert & Shrestha 1991;Chenevert & Shrestha 1987). This large variance is not only because the cement volume shrinkage is significantly affected by the temperature and pressure conditions and the employed test method (Reddy et al 2009), but also because the reported values often include shrinkage before the initial set of cement (i.e., shrinkage within the thickening time).…”
Section: Cement Volume Shrinkagementioning
confidence: 99%